The Oxford handbook of gender, sex, and crime - Gartner, Rosemary, 1952-; McCarthy, Bill (New York : Oxford University Press, 2014)
This title offers an unparalleled and comprehensive view of the connections among gender, sex, and crime in the United States and in many other countries. Its insights illuminate both traditional areas of study in the field and pathways for developing cutting-edge research questions.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on June 30, 2014).
Keywords: Crime -- Sex differences; Crime -- Sociological aspects; Criminal behavior; Female offenders